31P RINEPT MRSI and VBM reveal alterations in brain aging associated with major depression. Issue 4 (April 2015) - Biedermann, Sarah V.; Weber‐Fahr, Wolfgang; Demirakca, Traute; Tunc‐Skarka, Nuran; Hoerst, Mareen; Henn, Fritz; Sartorius, Alexander; Ende, Gabriele
Abstract : Purpose: Phosphomono‐ and diesters, the major components of the choline peak in 1 H magnetic resonance spectroscopy, are associated with membrane anabolic and catabolic mechanisms. With the refocused insensitive nuclei‐enhanced polarization transfer technique, these phospholipids are edited and enhanced in the 31 P MR spectrum. In depressed patients, alterations of the choline peak and cerebral volume have been found, indicating a possible relation. Thus, combining MR phosphorous spectroscopy and volumetry in depressed patients seems to be a promising approach to detect underlying pathomechanisms. Methods: Depressed in‐patients were either treated with antidepressive medication or with electroconvulsive therapy and compared to matched healthy controls. 31 P magnetic resonance spectroscopy imaging was conducted before and after the treatment phases. A 3D MRI dataset for volumetry was acquired in a dedicated 1 H head coil. Results: Phosphocholine and phosphoethanolamine were increased in depressed patients. Though patients responded to the treatments, phospholipids were not significantly altered. An increased age‐related gray matter loss in fronto‐limbic regions along with an altered relation of phosphomonoesters/phosphodiesters with age were found in depressed patients. Discussion: The findings of increased phosphomonoesthers and an age*group interaction for gray matter volumes need further research to define the role of phospholipids in major depression and possible associations to gray matter loss.Magn Reson Med 73:1390–1400, 2015. © 2014 Wiley Periodicals, Inc.